The Role of Sugar Transporter CsSWEET7a in Apoplasmic Phloem Unloading in Receptacle and Nectary During Cucumber Anthesis - Li, Yaxin; Liu, Huan; Yao, Xuehui; Sun, Lulu; Sui, Xiaolei (Frontiers in Plant Science, 2022)
During anthesis, there is an increased demand for carbohydrates due to pollen maturation and nectary secretion that warrants a systematic phloem unloading strategy for sugar partitioning. Sugar transporters are key components of the apoplasmic phloem unloading strategy and control the sugar flux needed for plant development. Currently, the phloem unloading strategy during anthesis has not been explored in cucumber, and the question of which sugar transporters are active during flower anthesis is poorly understood. In this study, a study utilizing the phloem-mobile symplasmic tracer carboxyfluorescein (CF) suggested that the phloem unloading was symplasmically isolated in the receptacle and nectary of cucumber flowers at anthesis. We also identified a hexose transporter that is highly expressed in cucumber flower, Sugar Will Eventually be Exported Transporter 7a (SWEET7a). CsSWEET7a was mainly expressed in receptacle and nectary tissues in both male and female flowers, where its expression level increased rapidly right before anthesis. At anthesis, the CsSWEET7a protein was specifically localized to the phloem region of the receptacle and nectary, indicating that CsSWEET7a may function in the apoplasmic phloem unloading during flower anthesis. Although cucumber mainly transports raffinose family oligosaccharides (RFOs) in the phloem, sucrose, glucose, and fructose are the major sugars in the flower receptacle and the nectary as well as in nectar at anthesis. In addition, the transcript levels of genes encoding soluble sugar hydrolases (α-galactosidase, sucrose synthase, cytoplasmic invertase, and cell wall invertase) were correlated with that of CsSWEET7a. These results indicated that CsSWEET7a may be involved in sugar partitioning as an exporter in the phloem of the receptacle and nectary to supply carbohydrates for flower anthesis and nectar secretion in cucumber.